Hydrothermal synthesis and characterization studies of α-Fe2O3/MnO2 nanocomposites for energy storage supercapacitor application. Issue 5 (1st April 2020) - Racik K, Mohamed; Manikandan, A.; Mahendiran, M.; Madhavan, J.; Victor Antony Raj, M.; Mohamed, M. Gulam; Maiyalagan, T.
Abstract: In this present study, semiconductor magnetic α-Fe2 O3 /MnO2 nanocomposites (NCs) were prepared by a facile hydrothermal (HT) method. The crystallographic structure, morphology, chemical configuration and magnetic features were analysed by X-ray powder diffraction (XRD), high resolution scanning electron microscope (HR-SEM), energy dispersive X-ray analysis (EDX), transmission electron microscope (TEM), Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS) and vibrating sample magnetometer (VSM) analyses. The as-prepared NCs were used as an electrode in energy storing supercapacitor was systematically examined. The electrochemical deeds of α-Fe2 O3 /MnO2 NCs was analysed by cyclic voltammetry (C–V) and galvanostatic charge–discharge (GCD) tests. The CV analysis of the NCs electrode showed a distinctive pseudocapacitive behaviour in 1 M KOH solution. The NCs electrode reveals enhanced specific capacitance compared to plain α-Fe2 O3 and MnO2 nanoparticles (NPs) and generates high specific capacitance of 216.35 Fg −1 . Pseudocapacitor obtains of energy density 135.42 Wh kg −1 at power density of 6.399 kW kg −1, indicating the as-prepared α-Fe2 O3 /MnO2 NCs shows noteworthy high-energy, specific capacitance, power densities and long-standing cyclic stability with 89.2% of preliminary capacitance reserved at 1A g −1 after 10000 cycles in judgement with the pure α-Fe2 O3 and MnO2 NPs electrode. The α-Fe2 O3 /MnO2 NCs electrode having noteworthy electrochemical characteristics performance renders promising applications in energy storing systems.